(untitled) (The Peerian Journal, 2022)
The article describes the construction of irrigation facilities, irrigation and irrigation works in the Surkhan region, under the rule of the Bukhara Emirate, based on the sources. An attempt was made to think about farming and efficient use of land based on natural and artificial irrigation in the Surkhan region. The Surkhan oasis, which is the southern region of Uzbekistan, has made a worthy contribution to world development with its unique culture, art, and invaluable social lifestyle. The economic, political and social policy of the Russian Empire in Turkestan is covered based on the sources.